Cubic Cu2O on nitrogen-doped carbon shells for electrocatalytic CO2 reduction to C2H4. (May 2019) - Ning, Hui; Wang, Xiaoshan; Wang, Wenhang; Mao, Qinhu; Yang, Zhongxue; Zhao, Qingshan; Song, Yan; Wu, Mingbo
Abstract: Electroreduction of carbon dioxide (CO2 ) to ethylene (C2 H4 ) is one of the most feasible approaches to reduce the carbon emissions and enhance carbon dioxide utilization, whereas the lack of efficient catalysts impedes the scale application. Cuprous oxide (Cu2 O) is a promising catalyst for the formation of C2 H4 but with unsatisfied selectivity and stability. Herein, we prepared Cu2 O/nitrogen-doped carbon shell (Cu2 O/NCS) composite and employed it in the production of C2 H4 from CO2 electroreduction. The ultra-thin NCS with graphene-like structure was prepared from petroleum asphalt by template method. The cubic Cu2 O nanocrystals are uniformly dispersed on the surface of NCS with ca. 150 nm diameters. Cu2 O/NCS loaded on glass carbon electrode showed a high faradaic efficiency of C2 H4 (24.7%) at −1.3 V ( vs . reversible hydrogen electrode) as well as remarkable stability. The excellent performance of Cu2 O/NCS is attributed to the high dispersion of cubic Cu2 O nanocrystals and the abundant pyridinic-N moieties in NCS. This work provides a new strategy to improve the selectivity and durability of Cu2 O for production C2 H4 from electrocatalytic CO2 reduction by fabricating composites with nitrogen-doped carbon materials. Graphical abstract: Image 1